Cover Image. (8th August 2019) - Gao, Zhifan; Liu, Xin; Qi, Song; Wu, Wanqing; Hau, William Kongto; Zhang, Heye
Abstract : The cover image is based on the Advanced Bio‐Signal Processing Techniques In Medical Applications Automatic segmentation of coronary tree in CT angiography images by Zhifan Gao et al., DOI10.1002/acs.2762 .